Extracellular Ubiquitin: Role in Myocyte Apoptosis and Myocardial Remodeling. Issue 1 (15th December 2015) - Scofield, Stephanie L.C.; Amin, Parthiv; Singh, Mahipal; Singh, Krishna
ABSTRACT: Ubiquitin (UB) is a highly conserved low molecular weight (8.5 kDa) protein. It consists of 76 amino acid residues and is found in all eukaryotic cells. The covalent linkage of UB to a variety of cellular proteins (ubiquitination) is one of the most common posttranslational modifications in eukaryotic cells. This modification generally regulates protein turnover and protects the cells from damaged or misfolded proteins. The polyubiquitination of proteins serves as a signal for degradation via the 26S proteasome pathway. UB is present in trace amounts in body fluids. Elevated levels of UB are described in the serum or plasma of patients under a variety of conditions. Extracellular UB is proposed to have pleiotropic roles including regulation of immune response, anti‐inflammatory, and neuroprotective activities. CXCR4 is identified as receptor for extracellular UB in hematopoietic cells. Heart failure represents a major cause of morbidity and mortality in western society. Cardiac remodeling is a determinant of the clinical course of heart failure. The components involved in myocardial remodeling include—myocytes, fibroblasts, interstitium, and coronary vasculature. Increased sympathetic nerve activity in the form of norepinephrine is a common feature during heart failure. Acting via β‐adrenergic receptor (β‐AR), norepinephrine is shown to induce myocyte apoptosis and myocardial fibrosis. β‐AR stimulation increases extracellular levels of UB in myocytes, and UB inhibits β‐AR‐stimulated increases in myocyte apoptosis and myocardial fibrosis. This review summarizes intracellular and extracellular functions of UB with particular emphasis on the role of extracellular UB in cardiac myocyte apoptosis and myocardial remodeling. © 2016 American Physiological Society. Compr Physiol 6:527‐560, 2016.